Implementation of the MBKM program: Meeting the needs and expectation of stakeholders - Rusfandi, Rusfandi; Muzammil, Lasim; Sholeh, Agus (Jurnal Inspirasi Pendidikan, 2023)
This research aims to gain an overview and constructive, pedagogical, and applicable feedbacks from stakeholders, both internal and external, of the Merdeka Belajar Kampus Merdeka (MBKM) program that has been implemented so far in every study program within the Faculty of Language and Literature (FLL) of a private university in Malang. The results of this study would be used as a basis for policy formulation and improvement of the quality of MBKM implementation in the future. The study applied a descriptive quantitative method with questionnaires as the data collection technique. Respondents include students (N=150), lecturers (N=25), academic staff within the faculty (N=7), non-university partners (N=15), and university partners (N=4). The results show that the MBKM program implemented at the FLL was relevant to what was expected by all the stakeholders, with a total score of 3.38 on the scale between 1 (very unsatisfactory) and 4 (very satisfactory), which means that the satisfaction level of the MBKM implementation at the FLL was satisfactory. Several obstacles were also identified concerning the MBKM program implementation as feedback for quality improvement in the future. Keywords: the MBKM program; the MBKM program implementation; stakeholders’ satisfaction